Damage-softening constitutive model of palm fiber reinforced concrete based on weibull distribution and its correction method - Qinghua Zhan; Xiaole Huang; Zhitao Huo; Feiting Yi; Huijuan Bo; Jing Jing; Guanzhi Luo; Jun Dai (PLoS ONE, 2025)
Based on the Weibull random distribution of the micro-unit strength of fiber reinforced concrete, the parameters are introduced to describe the micro-unit strength of concrete reasonably, and it is used to establish a damage-softening constitutive model that can reflect the whole process of fiber reinforced concrete damage with the Drucker-Prager yield criterion. On this basis, according to the stress-strain curves of concrete with different palm fiber content and cement content, the functional relationship is discussed among the parameters with palm fiber content and cement content of concrete damage-softening model based on Weibull distribution, then a more realistic concrete damage- softening constitutive model is established with the modified model parameters. To consider the dynamic characteristics of micro-elements in palm fiber concrete during loading-unloading, a modified linear regression model parameter solving method is proposed. By comparing the experimental results with the calculated values, the rationality of the constitutive model and the parameter solution method is verified. The constitutive model proposed in this paper can well reflect the stress-strain relationship and damage evolution process of plam fiber reinforced concrete under different mix ratios, which can provide reference for the engineering application of brown fiber concrete.